Analysis of Laws of Specialization for Presidential Candidates in the 2019 General Election in Bandung - Indonesia - Prakarsa, Ega; Suryadi, Karim; Anggraeni, Leni (Universitas Negeri Semarang, 2019)
Laws of specialization is one indicator in personal branding that includes ability, behavior, lifestyle, mission, achievement, profession and service. Laws of specialization is an important indicator of personal branding that must be known by various segments of voters in the community as a source of information relating to the president and vice president. But in reality, laws of specialization experience a distortion of meaning so that these personal characteristics become biased and are often associated with various political interests. This often leads to conflicts that are based on differences in understanding, as well as the emergence of an attitude of distrust of presidential candidates and vice presidential candidates for the 2019 general election. This study uses a quantitative approach, descriptive statistics. Through this research, the people of Bandung City already know and are able to distinguish and provide responses about the laws of specialization of presidential and vice presidential candidates in the 2019 general election. This research has implications for community leaders, political figures and the government.